Trichoderma: diversidade genética e fusão de protoplastos - Almeida, Kize Alves (2016)
Trichoderma is a fungal genus that attracts the attention of researchers worldwide due to its diversity and potential industrial, medical and biotechnological importance. In this work, divided into three chapters, we sought to review the literature in the first chapter; study the diversity of Trichoderma spp. associated with cacao (Theobroma cacao) in the second; and improve Trichoderma isolates used in commercial formulations for low temperature tolerance through protoplast fusion in the third chapter. For the diversity studies, samples of sapwood and dead cacao branches were collected in a plantation located in Ilheus (Bahia) to obtain one hundred isolates morphologically similar to Trichoderma species. A total of 83 endophytes from sapwood and 17 epiphytes from dead branches were obtained. The identification was based on the sequencing of the ITS and TEF regions and phylogeny was based on the alignment performed with 896 base pairs. The identified species belong to five clusters: 1) Harzianum, 2) Virens, 3) Longibrachiatum, 4) Brevicompactum and 5) Trichoderma. Trichoderma lentiforme represented 56.6% of all endophytes and most of the epiphytes isolates were identified as T. parareesei. Six putative novel species were identified among the isolates and these will be further investigated and described in the future. Studies with protoplasts were performed with isolates 427 (T. harzianum) and 691PR (T. asperellum), selected on the basis of mycelial growth diameter at 10°C and resistance to fungicides, respectively. The highest protoplast release was observed after 20-24 h of spore incubation and after 2 h of digestion using MgSO4 as osmotic stabilizer. These results contribute to increase our knowledge on the diversity of Trichoderma in association with cacao and begins to explore the improvement of a commercial formulation by protoplast fusion.